Protes sosial yang digambarkan dalam cerpen Tamil terbitan akhbar Tamil Nesan - Ravichandran Subramaniam (N/A, 2016)
Protes sosial yang digambarkan dalam cerpen Tamil terbitan akhbar Tamil Nesan by Ravichandran Subramaniam